(In)Definition an investigation on the word-image dialectic - Soroño, Abigail Joyce B. (College of Fine Arts, University of the Philippines Diliman, 2017)
Hypothetically, text-based paintings, prints, and sculptures locate in a no-man's land amidst visual images and language. When taken from their traditional context, text-based art transforms its literary function to something that is neither art nor language, a compound. This is noticeable in various platforms of media, whether it be print, television, or the internet. Billboard, advertisements, and movies, etc, are obvious examples where text and image collaborate. Through juxtaposed words and selected visual representations, various meanings and interpretations are made. This thesis is aimed at analysing the ideas behind the word-image dialectic with the viewer, and how one receives and finds meaning through a juxtaposition of each. By taking Filipino and English terms that are often heard and used today and placing them alongside visual representations, this project allows for careful interpretation of each to convey suggestive meanings